Nierozerwalność małżeństwa w pismach łacińskich ojców Kościoła z IV wieku - Dzierżon, Ginter (Ius Matrimoniale, 2015)
The author of the presented article discusses the issue of indissolubility of marriage in the writings of 4th century Latin Church Fathers. His analyses proved that among patrologists there are mixed opinions concerning the value of some writings on this topic. The majority of patrologists believes that, apart from Ambrosiaster, all other writers of that time gave no consent for people to remarry while some patrologists think the opposite. On the basis of the research carried out by H. Crouzel, the author pointed out that, apart from Ambrosiaster, all Church Fathers agreed that the texts of Mt 5, 32 and 19, 9 should be interpreted as an exception to the rule of not abandoning the spouse. Only Ambrosiaster stood for entering into a new marriage not only in the case of adultery but also for a few other reasons. Some patrologists think that his writings reflect certain practices adopted in the Church of that time. In this case, however, it was not a common practice but, as Kamas believes, a kind of laxism which appeared in the practice of a local Church.